2022
DOI: 10.3390/ijerph19074375
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Perceived Stress and Lifestyle Behaviors in Response to the COVID-19 Pandemic in The Netherlands: An Online Longitudinal Survey Study

Abstract: The COVID-19 pandemic has substantial implications for physical and mental wellbeing. This study investigated changes, over time, in lifestyle behaviors and perceived stress during the initial phase of the pandemic and associations with COVID-19 symptoms, in the Dutch general population. An online longitudinal survey study was performed with pre-lockdown measurements in February, and subsequently in April and June 2020 (n = 259, mean age 59 ± 14 years, 59% women). Self-report questionnaires were used to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
1
8
1
Order By: Relevance
“…Correlational analyses revealed significant associations of all constructs with the HST index, suggesting that a more positive psychological profile contributed not only to adopting healthier food consumption behaviors, but also to making more sustainable food choices. Prior works support these findings by underlining the effects of emotional aspects on food habits and choices [14,15,17,58]. Accordingly, it is acknowledged how experiencing negative emotions may lead to overeating.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Correlational analyses revealed significant associations of all constructs with the HST index, suggesting that a more positive psychological profile contributed not only to adopting healthier food consumption behaviors, but also to making more sustainable food choices. Prior works support these findings by underlining the effects of emotional aspects on food habits and choices [14,15,17,58]. Accordingly, it is acknowledged how experiencing negative emotions may lead to overeating.…”
Section: Discussionmentioning
confidence: 84%
“…To date, what has been scarcely addressed, however, is the relationship between the adoption of sustainable food choices and psychological factors. More broadly, diverse studies have exclusively explored the associations of an individual's psychological responses to the COVID-19 pandemic with lifestyle and health behavior changes [14][15][16][17], adopting, however, an individual-centric framework. As specifically concerns the changes in dietary behaviors, recent studies showed that stay-at-home restrictions, including teleworking and as social isolation, in some cases, to have triggered stress, anxiety and mood disorders throughout the population [18], ultimately affecting food choices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors explained this finding by assuming that adolescents commonly experience stress regardless of the pandemic, and thus pandemic-related stressors did not greatly affect their normative stress levels. To the best of our knowledge, no studies have scrutinized in adults the potential heterogeneity of trajectories (i.e., change over time) of perceived stress during the pandemic, and the findings of the previous variable-centered longitudinal studies on perceived stress are inconsistent ( 14 , 15 , 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, CFD simulation of the effect of using an air-purification device which also has the effect of altering the air-flow contours has not been investigated. Further, recent studies which focused on the concern to public health posed by the COVID-19 pandemic [ 24 , 25 ] do not approach this from the CFD perspective. In this work, we use CFD to examine the air-flow behavior in a room shared by two occupants, in which an air decontamination device, called a Polyester Filter and UV light (PFUV) dehumidifier is used.…”
Section: Introductionmentioning
confidence: 99%